The effects of the China-Pakistan Economic Corridor on India-Pakistan relations - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2016)
The China-Pakistan Economic Corridor (CPEC) constitutes one of the largest foreign investments China has made in the framework of the "One Belt, One Road" initiative. The expenditures planned for the coming years in the amount of approximately 46 billion will further intensify relations between China and Pakistan. At the same time, Pakistan will assume a more prominent role in China's foreign policy. But CPEC also affects relations between India and Pakistan. The transport corridor between Pakistan and China traverses Jammu and Kashmir, the status of which has been a subject of contention between India and Pakistan since 1947. This constellation would seem to suggest a negative scenario whereby CPEC could place additional strain on India-Pakistan relations. On the other hand, a positive scenario is also conceivable, with a settlement of the Kashmir dispute even becoming possible in the long term. (SWP Comments)
Keywords: 320